2016
DOI: 10.1002/rcm.7592
|View full text |Cite
|
Sign up to set email alerts
|

Ion trap mass spectrometry of surfactins produced by Bacillus subtilis SZMC 6179J reveals novel fragmentation features of cyclic lipopeptides

Abstract: The detected new natural lipoheptapeptide compounds with modified structures have significant potential for biotechnological and biocontrol applications. The complementary ITMS(2) data as well as the described internal fragmentation mechanism obtained from the sodiated surfactin molecules may further facilitate the structural elucidation of cyclic lipopeptides in the future. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 49 publications
4
47
0
Order By: Relevance
“…When the wrong sfp was changed for a correct copy from a surfactin-producer strain of B. subtilis , both surfactin and fengycin production were intensively expressed in the transgenic line of strain 168 (Coutte et al 2010). Our study revealed that a single base deletion in the sfp gene enables strain SZMC 6179J to produce active phosphopantetheine transferase and allows the production of the lipopeptides fengycin and surfactin, which was previously proved by TLC and HPLC investigations (Bóka et al 2016; Vágvölgyi et al 2013). This single base deletion in the sfp gene also makes strain SZMC 6179J a potential biocontrol candidate with good antifungal properties (Table 4).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…When the wrong sfp was changed for a correct copy from a surfactin-producer strain of B. subtilis , both surfactin and fengycin production were intensively expressed in the transgenic line of strain 168 (Coutte et al 2010). Our study revealed that a single base deletion in the sfp gene enables strain SZMC 6179J to produce active phosphopantetheine transferase and allows the production of the lipopeptides fengycin and surfactin, which was previously proved by TLC and HPLC investigations (Bóka et al 2016; Vágvölgyi et al 2013). This single base deletion in the sfp gene also makes strain SZMC 6179J a potential biocontrol candidate with good antifungal properties (Table 4).…”
Section: Discussionsupporting
confidence: 67%
“…The depsipeptide gene clusters enabling the production of surfactins and fengycins are present in the genome of B. subtilis SZMC 6179J. Although the presence of a given gene cluster in the genome does not necessarily mean the synthesis of the corresponding antibiotic, the effective production of two antibiotics very important for antimicrobial effectiveness, the antibacterial surfactin and the antifungal fengycin, were proved earlier in the case of strain SZMC 6179J (Bóka et al 2016; Manczinger et al 2011; Vágvölgyi et al 2013). The explored SNPs and DIPs do not disturb the efficient expression of these gene clusters, as the fengycins and surfactins are produced by the strain.…”
Section: Discussionmentioning
confidence: 99%
“…Then the supernatants were sedimented for 6 h at ambient temperature. Sedimentation was collected after centrifuge at 8000 × g for 10 min, then dissolved by methyl alcohol and the pH was adjusted to 7.0 (Lee et al, 2008; Bóka et al, 2016). The mixture was then stirred by magnetic stirrer at ambient temperature for 5 h. Sedimentation was removed after centrifuge at 8000 × g for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Collision-induced dissociation (CID) analysis has been applied to authenticate structures of lipopeptides homolog. By far, there are no reports of dipolymer or tripolymer lipopeptides produced by Bacillus (Li et al, 2008; Tosco et al, 2015; Bóka et al, 2016; Urajová et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The production of lipopeptide by Bacillus species is based on the strains: some strains can coproduce two or three classes of lipopeptides, while others can yield only one class [11][12][13]. B. licheniformis MB01 produces surfactin only [12], B. subtilis K1 coproduces surfactins and iturins, while B.…”
Section: Velezensismentioning
confidence: 99%